An ethical ground in Estlund’s epistemic procedimentalism? - Álvarez Osorio, Felipe (Revista Ethika+, 2023)
In this article it is argued that Estlund’s epistemic proceduralism, as a democratic model, requires minimum ethical dispositions that are not explicitly stated in the proposal. I will address the notion of Macpherson’s democratic model to illustrate this point. With this, it is noted that the minimum ethical disposition for this democratic model, which would shape an implicit ethical ground in epistemic proceduralism, are three: a disposition towards the knowledge involving the process; another towards the democratic procedure itself; and finally, one towards the recognition of the legitimacy of the results.